Aspek Hukum Corporate Social Responsibility Dalam Hukum Positif Indonesia - Almusawir SH (Universitas Atma jaya Makassar, 2011)
Company is considered as the source of damage to the environment, exploiting natural resources and merely concerned with corporate profits. Many companies involve and empower the community just to get sympathy, yet indeed it's the companiy's responsibility to give a different concept in which a company voluntarily donates something for a better community and cleaner environment. ..............................